Matryoshka-Type Liposomes Offer the Improved Delivery of Temoporfin to Tumor Spheroids - Yakavets, Ilya (Cancers (Basel), 2019)
The balance between the amount of drug delivered to tumor tissue and the homogeneity of its distribution is a challenge in the efficient delivery of photosensitizers (PSs) in photodynamic therapy (PDT) of cancer. To date, many efforts have been made using various nanomaterials to efficiently deliver temoporfin (mTHPC), one of the most potent photosensitizers. The present study aimed to develop double-loaded matryoshka-type hybrid nanoparticles encapsulating mTHPC/cyclodextrin inclusion complexes in mTHPC-loaded liposomes. This system was expected to improve the transport of mTHPC to target tissues and to strengthen its accumulation in the tumor tissue. Double-loaded hybrid nanoparticles (DL-DCL) were prepared, characterized, and tested in 2D and 3D in vitro models and in xenografted mice in vivo. Our studies indicated that DL-DCL provided deep penetration of mTHPC into the multicellular tumor spheroids via cyclodextrin nanoshuttles once the liposomes had been destabilized by serum proteins. Unexpectedly, we observed similar PDT efficiency in xenografted HT29 tumors for liposomal mTHPC formulation (Foslip(®)) and DL-DCL.